The death of Tun Abdul Razak: how Malaysians in madison learned the news. - Syed Arabi Idid, (Universiti Kebangsaan Malaysia, 1976)
A total of 75 per cent of Malaysian students at the University of Wisconsin, Madison, heard about the death of the Prime Minister, Y.A.B. Tun Haji Abdul Razak on the first day that he died. A majority learned of the news by word of mouth rather than from the mass-media.